Self-Differentiation Level and Its Contribution to the Prediction of Post-Traumatic Stress Symptoms among Refugees in Jordan - Al-Takhayneh, Suhaib; Faroun, Mohannad Mousa (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to assess the levels of post-traumatic stress disorder (PTSD) symptoms and self-differentiation among refugees in Jordan and to determine the extent to which self-differentiation contributes to predicting PTSD symptoms. Methods: A descriptive predictive research approach was utilized. Two scales were developed: one for self-differentiation and another for PTSD symptoms, and their psychometric properties, including validity and reliability, were verified. Levels were categorized into three categories: low level, represented by scores between 1 and 2.33; moderate level, represented by scores between 2.34 and 3.67; and high level, represented by scores between 3.68 and 5. The study sample consisted of 320 refugees, selected systematically from those seeking services at the Noor Al-Hussein Foundation/Family Health Institute across all its branches in Jordan. Results: The results indicated that both PTSD symptoms and self-differentiation among the study participants were at a moderate level. The mean score for self-differentiation was 2.73 with a standard deviation of 0.4, while the mean score for PTSD symptoms was 3.6 with a standard deviation of 0.46. It was also found that self-differentiation contributed significantly to explaining the variance in PTSD symptoms by 45.9%. Conclusion: Based on the study results, it is crucial to develop counseling programs for refugees aimed at reducing PTSD symptoms and assisting individuals in enhancing their self-differentiation, as it plays a significant role in reducing PTSD symptoms among refugees.